RELIGIOUS MODERATION RESEARCH (2016–2025): SYSTEMATIC REVIEW AND BIBLIOMETRIC MAPPING - Junaidi, Junaidi; Tanshzil, Sri Wahyuni; Ni Kadek Suwardani (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2025)
Religious moderation has gained increasing scholarly attention as societies confront rising polarization, yet existing research remains fragmented between normative discourse and policy-driven interpretations. Few studies systematically map how the field has evolved conceptually and how it intersects with interfaith harmony at a global level. This study addresses this gap by conducting a Systematic Literature Review using the PRISMA protocol combined with bibliometric analysis to examine Scopus-indexed publications on religious moderation from 2016 to 2025. The dataset consists of 235 peer-reviewed journal articles, and the analysis integrates descriptive statistics, thematic coding, and VOSviewer-based mapping of co-authorship and keyword networks. The findings show a rapid expansion of research after 2020, with Indonesia emerging as the dominant contributor and education-related contexts becoming the most frequently explored domain. Bibliometric mapping identifies three major thematic clusters: religious moderation in educational and civic settings, local wisdom and cultural practices, and digital-era challenges related to radicalism and polarization. Conceptually, the field is shifting from state-centered narratives toward relational ethics that emphasize interfaith coexistence. These results highlight the need for broader cross-regional collaboration and more comparative, theory-driven studies that move beyond national policy frameworks. The study concludes that religious moderation is evolving into a multidisciplinary lens for understanding interfaith relations and recommends future research focusing on leadership, digital citizenship, and community-based interfaith engagement. Abstrak Moderasi beragama semakin mendapat perhatian akademik seiring meningkatnya polarisasi sosial, namun penelitian yang ada masih terfragmentasi antara wacana normatif dan interpretasi berbasis kebijakan. Hanya sedikit studi yang secara sistematis memetakan perkembangan konseptual bidang ini serta keterkaitannya dengan harmoni antaragama pada tingkat global. Penelitian ini mengisi kesenjangan tersebut dengan melakukan Tinjauan Literatur Sistematis menggunakan protokol PRISMA yang dipadukan dengan analisis bibliometrik terhadap publikasi terindeks Scopus mengenai moderasi beragama pada periode 2016 hingga 2025. Dataset terdiri dari 235 artikel jurnal terbitan sejawat, dan analisis dilakukan melalui statistik deskriptif, pengodean tematik, serta pemetaan jejaring penulis dan kata kunci menggunakan VOSviewer. Temuan menunjukkan peningkatan pesat penelitian setelah tahun 2020, dengan Indonesia sebagai kontributor dominan dan konteks pendidikan sebagai domain yang paling sering dikaji. Pemetaan bibliometrik mengidentifikasi tiga klaster tematik utama yaitu moderasi beragama dalam konteks pendidikan dan kewargaan, kearifan lokal dan praktik budaya, serta tantangan era digital terkait radikalisme dan polarisasi. Secara konseptual, bidang ini bergerak dari narasi berpusat pada negara menuju etika relasional yang menekankan koeksistensi antaragama. Hasil ini menegaskan perlunya kolaborasi lintas kawasan dan penelitian komparatif yang lebih berorientasi teori di luar kerangka kebijakan nasional. Studi ini menyimpulkan bahwa moderasi beragama berkembang menjadi lensa multidisipliner untuk memahami relasi antaragama dan merekomendasikan penelitian lanjutan mengenai kepemimpinan, kewargaan digital, dan keterlibatan antaragama berbasis komunitas.